EVALUASI KEBIJAKAN TENTANG MANAJEMEN INOVASI PERGURUAN TINGGI (MIPT) DI PERGURUAN TINGGI NEGERI - Eva Yulinda; Sofjan Aripin; Wihatmoko Waskitoaji; Hedi Heryadi; Eko Kurniawan (Kebijakan : Jurnal Ilmu Administrasi, 2022)
ABSTRACT Policy Evaluation of the Ministry of Research, Technology and Higher Education Regulation No. 24 of 2019 aims to encourage The University (PT) to manage innovations that impact people's lives. The management of innovation in State Universities (PTN) is not optimal as expected. For this reason, the implementation of Higher Education Innovation Management (MIPT) is expected to play an optimal role in facilitating and realizing the improvement, development, and utilization of research results in PTN. Steps and strategies are taken by the Ministry of Research and Technology (Kemristek)/National Research and Innovation Agency (BRIN) to realize research innovations in PT, specifically by encouraging the implementation of Innovation Management in their respective PT. In addition, they are providing technical guidance in measuring innovation performance to provide the expected results, namely strengthening innovation at PT. The implementation of MIPT in PTN has been effectively implemented and has become the primary goal of PTN, but there are still obstacles in its implementation. Several factors of emphasis in increasing the productivity of innovation performance are related to the number of researches, inventions, innovation products, strengthening innovation management institutional policies, and organizational arrangements that require the formation of innovation management institutions. The challenges of PTN in MIPT are related to the stages of commercializing innovation products to the industrial world, managing Intellectual Property Rights and Patents. Some recommendations that need to be considered are the need for continuity of socialization, the availability of technical modules that provide detailed explanations of what PTN must do in managing innovation and clarity of authority over the Regulation No. 24 of 2019 concerning MIPT. Keywords: Evaluation, Higher Education Innovation Management, Policy